Impacts of shaft on mass transfer in a reverse osmosis rotating disk membrane - Joey Vei, Choo Er; Ng, Khai Ching; Chong, Yie Kai; Tan, Jia Xin; Lau, Woei Jye; Liang, Y. Y. (Ali Kargari, 2024)
A rotating disk has been proposed for integration within the membrane module due to its ability to induce shear near the membrane. This study focuses on the hydrodynamics and mass transfer simulation of a reverse osmosis (RO) rotating disk membrane system using three-dimensional computational fluid dynamics techniques. The mass transfer coefficient (k ̅_(mt,ave)), wall shear (γ ̅_(,ave)) and water flux ((J ̅_(,ave)) show significant deviations of at least double between cases with and without a shaft (at high disk rotational speed). This is because at a higher disk rotational speed, the flow for the case with shaft experiences a more uniform and exhibits circular velocity pathline caused by the high-speed circulating shaft, whereas a more non-uniform flow is obtained for the case without shaft. The significance of non-uniform flow lies in its ability to enhance the flow perpendicular to the membrane surface. This enhancement is evidenced by the stronger turbulent kinetic energy observed near the membrane surface when the shaft is absent especially at a higher disk rotational speed. The results also indicate that rotational direction (clockwise vs. anticlockwise) does not significantly impact γ ̅_(,ave), k ̅_(mt,ave) and J ̅_(,ave). Regarding the geometrical effect, it was found that reducing the gap between the membrane interface layer and the impeller decreases the size of the quiescent region near the membrane surface. This reduction results in stronger mixing near the membrane, which enhances mass transfer and increases water flux.